Comparative water management study at farm level in paddy and upland rice from the view point of yield - Imtiyaz, Mohammad; Apichart Anukularmphai; I, Fude; Nielsen, Jens Moller; Thailand (King 's Scholarships) (Bangkok : Asian Institute of Technology, 1977)
Present research work is based on water management in lowland paddy and UPLAND rice fields from view point of yield. This LITERATURE study is made according to varieties, method of cultivation, amount of fertilizer applied, amount of water applied during different stages of plant growth and assuming soil and climate are the same in both fields. In lowland paddy fields water is flooded throughout the crop growing period and in UPLAND rice fields limited amount of water is available for crop production, it is necessary to adopt the flood and drought tolerance varieties for paddy and UPLAND rice respectively for optimum benefit. Method of cultivation is also dependent upon the amounts of water available for crop production. Transplanting or broadcasting and drilling or broadcasting method of seeding are generally practiced in paddy and UPLAND rice fields respectively. Direct broadcasting method of seeding appears suitable in both fields for maximum possible benefit. Date of planting, seed rate and spacing also affect the grain yields. In UPLAND fields, marginal rate of return is calculated at different amounts of water applied and it was observed that the marginal rate of return decreases as amount of water applied increases. Hence for maximum benefit it is necessary to choose the proper amount of water for crop production. Marginal rate of return of yield is also a function of variety and amount of fertilizer applied. In UPLAND rice field, it was observed that when water is distributed over a number of fields instead of giving it all to one field, the total yield is more. But how much water is reduced from one field and used on the other fields is dependent on cultivation cost and government policy. The ratio of percent reduction in yield to the percent reduction in water is a function of varieties, soil, and climate and amount of fertilizer applied in the field. It was also observed that if fertilizer is used the water requirement can be reduced for the same production level. This means more water can be reduced from one field and used on the other fields with the application of fertilizer. It was observed that the intermittent method of flooding gives higher yield in lowland paddy field. It was also observed that paddy performance is a function of irrigation interval, varieties, amount of fertilizer applied and the depth of flooding in the fields. After a certain depth of water, the marginal rate of return of yield becomes negative, hence after a certain water depth it is necessary to drain the excess water from the fields. The performance in lowland paddy field does not simply depend on total amount of water but also depends on the amount of water applied at different stages of the crop.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1978
Keywords: Irrigation farming